Valuable offsprings of Seyve-Villard 12375 - Hajdu, E. (International Journal of Horticultural Science, 2004)
Powdery mildew, Phylloxera and downy mildew epidemics devastated large areas of vineyards in Hungary in the 1800s. To establish new plantages resistant so called "direct producers" were imported from America (direct means "without grafting"). Direct producers have secure yield but their quality is inferior. After World War II, an organized breeding programme was started to replace them and parallel to this the law prohibited their production. As a resistance gene source, the E.2 clone (S. V. 12375 E.2) of Seyve-Villard 12375, Franco-American hybrid selected in Eger was used by Hungarian breeders. Several valuable hybrid families have originated from crosses of this variety hybrid.In the Research Institute for Viticulture and Enology at Kecskemét, two valuable table grape hybrids were registered under the names of R.65=Esther and R.78=Fanny coming from 2 hybrid families of the parent S. V. 12375 E.2. Both varieties may be cultivated "environmentally".